Job Strain as a Risk Factor for Type 2 Diabetes: A Pooled Analysis of 124,808 Men and Women - Nyberg, Solja T.; Fransson, Eleonor I.; Heikkilä, Katriina; Ahola, Kirsi; Alfredsson, Lars; Bjorner, Jakob B.; Borritz, Marianne; Burr, Hermann; Dragano, Nico; Goldberg, Marcel; Hamer, Mark; Jokela, Markus; et al. (Diabetes care, 2014)
The status of psychosocial stress at work as a risk factor for type 2 diabetes is unclear because existing evidence is based on small studies and is subject to confounding by lifestyle factors, such as obesity and physical inactivity. This collaborative study examined whether stress at work, defined as "job strain," is associated with incident type 2 diabetes independent of lifestyle factors. We extracted individual-level data for 124,808 diabetes-free adults from 13 European cohort studies participating in the IPD-Work Consortium. We measured job strain with baseline questionnaires. Incident type 2 diabetes at follow-up was ascertained using national health registers, clinical screening, and self-reports. We analyzed data for each study using Cox regression and pooled the study-specific estimates in fixed-effect meta-analyses. There were 3,703 cases of incident diabetes during a mean follow-up of 10.3 years. After adjustment for age, sex, and socioeconomic status (SES), the hazard ratio (HR) for job strain compared with no job strain was 1.15 (95% CI 1.06-1.25) with no difference between men and women (1.19 [1.06-1.34] and 1.13 [1.00-1.28], respectively). In stratified analyses, job strain was associated with an increased risk of diabetes among those with healthy and unhealthy lifestyle habits. In a multivariable model adjusted for age, sex, SES, and lifestyle habits, the HR was 1.11 (1.00-1.23). Findings from a large pan-European dataset suggest that job strain is a risk factor for type 2 diabetes in men and women independent of lifestyle factors.